(3GdSfOGJ GdYGOjI hOhQgG aj GdEKHGJ GdeOfj (B:s (3OQGSI ebGQfI HGdJTQjYGJ GdYQHjI GdCLfHjI hCMcGe GdbVGA (B/s - (3GdYHhOj, YHGSs ((3YeGf(B: s (3GdOGQ GdYdejI GdOhdjI hecJHI OGQ GdKbGaI(B, s, 2001)
(3GdSfOGJ GdYGOjI GdeYOI ddGKHGK, TQhW GfTGA GdSfO GdYGOj, MLjI GdSfO GdYGOj aj GdGKHGK, GdSfOGJ GdYGOjI ZjQ GdeYOI ddGKHGK, GdQSGFd hGdHQbjGJ, GdOaGJQ hGdChQGb ZjQ GdehbY YdjgGs
(3GdeQGLY U(B.227s
Keywords: (3GdChQGb GdeGdjIs; (3GdSfOGJs